Mapping the “Aksi Bela Islam 212” effect: Redefining identity politics in Indonesian scholarship 2011–2023 - Ari Ganjar Herdiansah; Muhammad Andi Firmansyah; Noor Sulastry Yurni Ahmad (Universitas Negeri Yogyakarta, 2026)
While identity politics has been central to modern political disputes, little work has systematically explored how its discursive deployment has limited interpretations in Indonesia. This paper seeks to fill that gap by examining changes in Indonesian academic discourse from 2011 to 2023 through a systematic literature review and content analysis of 60 peer-reviewed scholarly articles, adopting a Foucauldian genealogical method. Our findings reveal that in the initial phase of our baseline period (2011–15), identity politics was commonly represented as a cultural and ethnic phenomenon or, alternatively, as a natural outcome of plural democracy. A significant rift occurred in 2016–2017, when the “Aksi Bela Islam 212” (action to defend Islam) and the Jakarta gubernatorial election mobilised religious identities and harnessed them as a major academic frame. By 2019, scholarly opinion had little else to call identity politics than religio-electoral arrangements in the register of polarisation and democracy’s perils. However, termination, along with alternative expressions such as gender and ethnic empowerment, received considerably less attention until more recently. The narrowing identifies how Indonesian scholarship has prioritised high-stakes religious electoral politics over broader and more emancipatory identity politics. The research, therefore, highlights how discourse, power, and knowledge production interpenetrate to shape identity politics in post-authoritarian Indonesia.